PRESERVING NUTMEG : HISTORICAL SIGNIFICANCE, MEDICINAL BENEFITS, AND CLIMATE CHANGE THREATS TO INDONESIAN NUTMEG - Nuralfin Anripa; Vicka Frantya Lone (International Journal of Islamic and Complementary Medicine, 2024)
Over the past thousand years, scholars and practitioners, drawing from diverse fields including culture, philosophy, sociology, and history, have meticulously documented the intricacies of various medicinal substances and their applications. In this continuum of knowledge, nutmeg, a quintessential spice of Indonesian heritage, has held a prominent place. This study aims to explore the historical significance of nutmeg in Indonesia, its role in medicinal practices, and the threats posed by climate change to nutmeg cultivation. The research seeks to provide valuable insights into the cultural and historical importance of nutmeg in Indonesian society, as well as its medicinal benefits. Additionally, the study aims to analyze the potential impact of climate change on nutmeg production in Indonesia. The study uncovered nutmeg's diverse significance in Indonesia across historical, cultural, medicinal, and economic realms. It emphasized nutmeg's medicinal potential and the climate change challenges to its production. Findings stressed the necessity of robust climate policies and proactive adaptation strategies to ensure nutmeg farming sustainability. In conclusion, this study highlights nutmeg's historical, medicinal, and climate change-related challenges in Indonesia. It stresses the necessity of comprehensive measures to address climate change impacts and integrate resilience strategies into nutmeg farming practices and policymaking. These findings offer valuable guidance for policymakers and stakeholders to ensure the sustainable growth of Indonesian nutmeg exports amidst environmental changes.